Análise dos atendimentos a mulheres em situação de violência pelo parceiro íntimo em uma unidade hospitalar - Cínthia Neves Fonseca (2021)
Violence against women, particularly intimate partner violence (IPV), constitutes a serious public health problem and a violation of women's human rights. IPV comprises physical aggression, sexual coercion, psychological abuse and controlling behaviors towards women by a partner or ex-partner, resulting in physical, sexual or psychological harm, among others. In relation to physical violence, admittedly a cyclical phenomenon, it involves any conduct that offends the health or bodily integrity of women, up to femicide – murder of women due to their gender. Thus, reviews of hospital records would allow us to measure the impact of IPV on women's health, knowledge about the need for health care in urgent and emergency services associated with this type of violence, capable of characterizing the complex nature of the treatment and high cost to women, services/health system, communities and society. Knowing the characteristics of the aggression, the relationship between the woman and the perpetrator, the potential demand for urgent and emergency hospital care and the consequences for the morbidity and mortality of women, the institutions and the health system, is necessary to understand the real harm, with a view to prevention efforts, care and appropriate interventions. The study aimed to understand the panorama of care for women physically attacked by an intimate partner in a large public hospital that is a reference in urgent and emergency care. This is a cross-sectional, descriptive study with a clinical approach, which analyzed the medical records of 205 women, aged 15 years or older, who were assisted due to a situation of violence by their partner. The period from 2016 - the 10-year mark of the Maria da Penha Law - to 2019 was analyzed, considering sociodemographic variables related to the episode of aggression, hospital care, complications and the outcome. Data were subjected to descriptive analysis, using the Stata® program, with presentation at two different times: sociodemographic data, relating to violence and care in the emergency room of all women attended; and data related to assistance to those who needed hospitalization. Young women were more vulnerable to intimate partner violence, 72.68% under 40 years old and including those under 18 years old (4.39%), and 44.39% had some comorbidity, mainly psychiatric disorders (56.04%). Women who did not work (23.90%) or with informal work (29.76%), married or in a stable union (54.63%), with children with the aggressor (60.31%) were more affected, residence the most frequent place of violence (68.78%) and 48.29% consisted of cases of recidivism. Direct aggression or beating prevailed (46.34%), in addition to the additional use of sharp and blunt objects (54.63%), with injuries to the face (41.95%), head (39.02%) and upper limbs (33.66%). There were burnt women (9.27%), most of them high severity burnt (63.16%). The most urgent priority risk classification/orange prevailed (65.25%), attended by the specialty of general surgery and trauma (67.80%). In 69.76% of the cases there was no record on admission that it was aggression by a partner, which was later evidenced in a multidisciplinary approach, and 49.76% of the women demanded hospitalization; 69.61% surgery(s); 26.47% intensive care; and 60.78% had some complication. As an outcome, hospital discharge prevailed (88.29%), with return appointments (71.58%), readmission (14.74%) and there were eight deaths (3.90%), with 50% of deaths in the last year (2019). The analysis of the assistance allowed to identify that women assaulted by their partner demand a series of specialized, urgent and emerging care and assistance, with critical and invasive care, configuring the magnitude of the violence suffered by women, which reinforces the deleterious impact of gender and the real disastrous consequences of IPV for women, in their health and in their lives, impacting the entire society. By portraying the magnitude of IPV, this study can contribute to greater visibility of the problem, appropriate approach to cases in hospital services by multidisciplinary teams, in addition to the treatment of physical injuries. The importance of reference hospitals in urgent and emergency care as a place of detection of cases of violence, reception, treatment, care and one of the points of composition of the intersectoral network for confronting and breaking the cycle of violence, its escalation in severity and the prevention of femicide. The study results support the need for investment and improvement of strategies, devices and tools to address this complex public health problem.